A glimpse of the Y-generation in Higher Education: some implications on teaching and learning environments - Maurtin-Cairncross, Anita (South African Journal of Higher Education, 2016)
Every generation has unique and different characteristics which distinguishes them from every other generation. This may result in respective wants and needs which may differ considerably. Students born between 1980 and 1996 (sometimes 1982-2000) have often been labelled as: the NetGeneration (Net Gen), Gen Y, Millennials or digital natives. These labels reflect the younger generation’s upbringing, where communication technology is the norm. Research indicates that traditional teaching methods and materials need to be adapted to improve the match of the needs and preferences of Generation-Y students. Therefore a research study was done to provide broad trends in students’ perceptions of the inclusion e-learning technologies in their courses and their use of interactive social media sites. The study illustrated that the majority of the participants access and use social network sites regularly. The findings may therefore be used to illustrate the importance of the inclusion of electronic, social network-based and mobi-type teaching and learning opportunities. University staff therefore need to take heed of generational trends and the impact of the learning needs of the Generation-Y in this sector, as many of these students are currently in the Higher Education system. Key words: Generation Y, netgen, Higher education, teaching and learning environments, communication technology, social media